2020
DOI: 10.21037/tlcr-20-867
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary oligometastases treated by stereotactic body radiation therapy (SBRT): a single institution’s experience

Abstract: Background: To investigate the effect of stereotactic body radiation therapy (SBRT) on pulmonary oligometastases and to analyze the clinical factors and dose parameters affecting local recurrence-free survival (LRFS) and overall survival (OS). Methods: This study retrospectively enrolled a total of 84 patients (148 lesions) treated in our department from May 2015 to November 2018. Pulmonary oligometastases was defined as up to 5 metastatic lesions in the lung and with both the primary tumor and any extra-thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The local control (LC) rate of SBRT for pulmonary lesions is high, although slightly different rates are shown depending on the histology: the LC rate at 3 years was >85% in solitary primary lung cancer, 14 and the LC rate at 2 to 3 years was 59% to 80% in oligometastatic pulmonary tumors. 23 , 24 , 25 , 26 , 27 A biological effective dose with an α/β ratio of 10 Gy (BED 10 ) < 100 Gy to the target volume and pulmonary metastasis that originates from tumors less responsive to radiation therapy, such as colorectal cancer, are associated with a poor LC rate. 24 , 25 , 28 , 29 As for OS, previous reports on oligometastatic pulmonary tumors showed widely ranging OS rates of 50% to 70% at 2 to 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local control (LC) rate of SBRT for pulmonary lesions is high, although slightly different rates are shown depending on the histology: the LC rate at 3 years was >85% in solitary primary lung cancer, 14 and the LC rate at 2 to 3 years was 59% to 80% in oligometastatic pulmonary tumors. 23 , 24 , 25 , 26 , 27 A biological effective dose with an α/β ratio of 10 Gy (BED 10 ) < 100 Gy to the target volume and pulmonary metastasis that originates from tumors less responsive to radiation therapy, such as colorectal cancer, are associated with a poor LC rate. 24 , 25 , 28 , 29 As for OS, previous reports on oligometastatic pulmonary tumors showed widely ranging OS rates of 50% to 70% at 2 to 3 years.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 , 28 , 29 As for OS, previous reports on oligometastatic pulmonary tumors showed widely ranging OS rates of 50% to 70% at 2 to 3 years. 23 , 24 , 26 In this study, 6 patients (15%) were treated with 8 fractions (BED 10 < 100 Gy) owing to the central location, and 8 patients (21%) with pulmonary metastasis that originated from tumors less responsive to radiation therapy (colorectal cancer and renal cancer) were included. Although a direct comparison between the studies is difficult owing to the different patient backgrounds and treatment, the incidence of LR in this study was relatively low compared with these previous reports, and the OS was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Chai et al discussed the therapeutic effects of SBRT on pulmonary metastatic tumors. Univariate analysis showed that age ≥ 63 years, primary colorectal cancer, BED10 < 85.2 Gy, adenocarcinomas, PTV min BED10 < 76.6 Gy, and GTV ≥ 8.8 cc were signi cantly correlated with local recurrence-free survival (LRFS) (23). This study found that patients who were younger than 57 years of age (p = 0.037, HR = 3.35, 95% CI = 1.08-10.41) and those whose metastatic organs were the lungs (p = 0.046, HR = 3.15, 95% CI = 1.02-9.76) had a better overall survival time, which is consistent with the ndings of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Inderson et al's report an endoscopic ultrasound guided radiofrequency ablation for left adrenal oligometastasis following EA with acceptable outcome [49]. Pulmonary oligometastases treated with SBRT also appear to be safe and feasible for local control with minimal toxicity [50]. Larger SBRT studies that include synchronous metastasis or oligorecurrence of esophageal carcinoma have demonstrated the safety and efficacy of this treatment strategy [51].…”
Section: Evidence For Management Of Oligometastasismentioning
confidence: 99%